PENGARUH AKSESIBILITAS, EXPERIENTIAL MARKETING DAN ELECTRONIC WORD OF MOUTH (eWOM) TERHADAP KEPUTUSAN BERKUNJUNG KEMBALI MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING - Dewi Tantriana; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2019)
Today the growth of tourism is increasing in both terms of patterns, shapes and activities. People start making tourism part of the necessities of life. As one of the tourist attractions in Semarang district, the Umbul Sidomukti has provided attractive vehicles that are expected to shape positive experiences, resulting ina visitor's satisfaction and interest ina return visit. The purpose of this study is to find the effects of accessibility, experiential marketing, and electronic word of mouth on the decision to visit back through customer satisfaction. The number of samples is 100 responders with purposive and unsampling techniques. This type of research is explanatory research. This study use SPSS 24.0 software for Windows. Research results indicate that partial accessibility, experiential marketing, electronic word of mouth had a significant effect against customer satisfaction. While simultaneously accessibility, experiential marketing, and electronic word of mouth, had a significant effect against customer satisfaction